A novel methodology for imaging newly bone formation around bioceramic bone substitutes - Gorustovich Alonso, Alejandro Adrian; Sivak, Matias Gabriel; Guglielmotti, Maria Beatriz (Wiley-liss, Div John Wiley & Sons Inc, 2006)
Fil: Gorustovich Alonso, Alejandro Adrian. Comisión Nacional de Energía Atómica; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina